19 COMPARATIVE COST ANALYSIS OF ALTEPLASE VERSUS TENECTEPLASE FOR ISCHAEMIC STROKE IN A SINGLE CENTRE TERTIARY HOSPITAL. (25th October 2022) - Kitt, K; Noone, I; Cassidy, T
Abstract: Background: Stroke thombolysis has been a proven effective treatment for acute stroke since 1995. Since then Alteplase has been the standard thrombolytic agent used in the hyperacute stroke patient, the dose being decided by body weight (0.9mg/kg). 10% of the dose is given as a bolus, and the remaining 90% given as an infusion. As the dose is weight based, more than one vial of Alteplase can be required. Tenecteplase is a more recent thrombolytic agent, and the 2017 large multi-centre randomised control trial NOR-TEST 2 indicated that Tenecteplase is similarly effective compared to Alteplase. Tenecteplase is given entirely as a bolus dose, with a maximum dose of 40mg administered, equivalent to one vial. A single of vial of Alteplase (Actilyse) costs €536, and a single vial of Tenecteplase (Metalyse) costs €986. Our study was set up to compare potential costs of the two treatments based on our patient cohort. Methods: We retrospectively looked at patients given Alteplase for acute ischaemic stroke in our institution in the year 2019 (n=29). We recorded the weight of the patient, and the number of vials used to administer the appropriate dose of Alteplase. We calculated the cost of the number of vials of Alteplase used over the year, and compared that to the cost of Tenectaplase, if that were to be used instead. Results: Over the course of the calendar year, 29 patients received Alteplase. All 29 patients had a requirement for two vials of Alteplase based on their admission weight, at a total cost of €31, 088 over the year 2019. The cost of Tenectaplase for the same patient cohort would have been €28, 594, with a potential cost saving of €2, 494. Conclusion: Based on our acute ischaemic stroke patient cohort for the year 2019, there is a potential cost saving benefit in a move towards using Tenecteplase instead of Alteplase.